2014
DOI: 10.1111/php.12397
|View full text |Cite
|
Sign up to set email alerts
|

Low‐level Laser (Light) Therapy Increases Mitochondrial Membrane Potential and ATP Synthesis in C2C12 Myotubes with a Peak Response at 3–6 h

Abstract: Low level laser (light) therapy has been used before exercise to increase muscle performance in both experimental animals and in humans. However uncertainty exists concerning the optimum time to apply the light before exercise. The mechanism of action is thought to be stimulation of mitochondrial respiration in muscles, and to increase adenosine triphosphate (ATP) needed to perform exercise. The goal of this study was to investigate the time course of the increases in mitochondrial membrane potential (MMP) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
99
2
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(115 citation statements)
references
References 32 publications
7
99
2
7
Order By: Relevance
“…In this way, some recent studies have reported improvement in performance after acute photobiomodulation [3,6,7]; however, the effects of photobiomodulation therapy on a high-intensity effort are still unclear [8], and based on the increase in ATP production [2], phosphocreatine resynthesis [4], and reduction in blood lactate concentration ([La − ]) [4,5], it is possible to assume that photobiomodulation therapy could also improve the high-intensity effort such as through the anaerobic capacity and time to exhaustion in a supramaximal effort.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In this way, some recent studies have reported improvement in performance after acute photobiomodulation [3,6,7]; however, the effects of photobiomodulation therapy on a high-intensity effort are still unclear [8], and based on the increase in ATP production [2], phosphocreatine resynthesis [4], and reduction in blood lactate concentration ([La − ]) [4,5], it is possible to assume that photobiomodulation therapy could also improve the high-intensity effort such as through the anaerobic capacity and time to exhaustion in a supramaximal effort.…”
Section: Introductionmentioning
confidence: 96%
“…Its effect has been associated with electron transport chain activity, increasing the oxidative metabolism and adenosine triphosphate (ATP) production [2], causing changes in the oxygen kinetics [3], phosphocreatine resynthesis [4], lactate production [4,5], and microcirculation [6], contributing to increases in the supply of energetic substrate in the muscle.…”
Section: Introductionmentioning
confidence: 99%
“…Transcranial LLLT promotes ATP biosynthesis and increases the expression level and activity of mitochondrial complex IV in mice prefrontal cortex in depressive mouse model [4]. To support this idea, Ferraresi et al illuminated that LLLT increases mitochondrial membrane potential and ATP synthesis in C2C12 myotubes [44]. Therefore, the therapeutic mechanism of LLLT on depression may be associated with an increase of ATP-production caused by low-level laser irradiation (LLLI) (Figure 2).…”
Section: Lllt Enhances Atp Biosynthesismentioning
confidence: 81%
“…Moreover, a recent study 41 has demonstrated that 3-6 h could be an optimum time to apply phototherapy in order to improve muscle metabolism before exercise. This study has also suggested possible cumulative effects if the illumination is applied at intervals of <24 h for muscle recovery after exercise.…”
Section: Lllt Exercise and Muscle Recovery 189 Discussionmentioning
confidence: 99%